Performance Evaluation of the Simplified Network Coding Technique in a TCP/IP-based Wireless Sensor Network - Jaroslaw KRYGIER (Communications of International Proceedings, 2021)
In this paper, a performance of the Network Coding technique that has been adapted to 6LoWPAN-based networks is discussed. The proposed solution named NC6LoWPAN, initially tested in a real wireless sensor network, is then investigated by simulations in terms of packet buffering time and traffic type - the parameters which influence the coding opportunity and finally the total coding gain. The results show that the coding gain in the network can be tuned by a time in which native packets can be buffered in intermediate nodes while waiting for encoding. The results also confirmed that the optimal buffering time is dependent on many factors, mainly on the protocol stack used for the transmission (UDP or TCP-based), network topology and traffic intensity.
Keywords: network coding; Wireless Sensor Networks; 6LoWPAN-based Internet of Things